2014
DOI: 10.1136/gutjnl-2014-306930
|View full text |Cite
|
Sign up to set email alerts
|

Fucosyltransferase 2 (FUT2) non-secretor status and blood group B are associated with elevated serum lipase activity in asymptomatic subjects, and an increased risk for chronic pancreatitis: a genetic association study

Abstract: These are the first results indicating that ABO blood type-B as well as FUT2 non-secretor status are common population-wide risk factors for developing chronic pancreatitis. They also imply that, even within the reference range, elevated lipase activities may indicate subclinical pancreatic injury in asymptomatic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 46 publications
3
54
0
4
Order By: Relevance
“…1 For rs632111, the same (non-significant) direction of effect was observed, while for rs8176693, the effect direction was reverse. Interaction and subgroup analysis revealed significant interaction effects of rs632111 with alcohol consumption ( p value 0.04, OR 0.82, 95% CI 0.68 to 0.99) and for rs8176693 for the subgroup of alcohol-dependent individuals ( p value 0.04, OR 0.78, 95% CI 0.62 to 0.98); however, these associations would not withstand correction for multiple testing.…”
mentioning
confidence: 83%
“…1 For rs632111, the same (non-significant) direction of effect was observed, while for rs8176693, the effect direction was reverse. Interaction and subgroup analysis revealed significant interaction effects of rs632111 with alcohol consumption ( p value 0.04, OR 0.82, 95% CI 0.68 to 0.99) and for rs8176693 for the subgroup of alcohol-dependent individuals ( p value 0.04, OR 0.78, 95% CI 0.62 to 0.98); however, these associations would not withstand correction for multiple testing.…”
mentioning
confidence: 83%
“…They represent mere risk factors without Mendelian inheritance and a significant percentage of the healthy population will carry these single nucleotide polymorphisms without ever developing pancreatitis. Among patients, the proportion of carriers is simply higher 20 . These genetic changes affect the genes for carboxypeptidase A1 ( CPA1 , the risk ratio [RR] for which increases 30-fold but prevalence is rare), the pancreatic secretory trypsin inhibitor SPINK1 (20-fold and common), carboxyl-ester lipase ( CEL , 6-fold and rare), chymotrypsinogen C ( CTRC , 5-fold and common), the cystic fibrosis transmembrane conductance regulator ( CFTR , 2–3-fold and common), the blood type ABO locus (2,7-fold for blood type B versus O and common) and the calcium sensing receptor ( CASR , 1.9-fold and common).…”
Section: Pathophysiology Of Chronic Pancreatitismentioning
confidence: 99%
“…Preliminary reports which await further validation include CTSB [60], MYO9B [61], and UBR1 [62], or the association of an increased pancreatitis risk with ABO blood group and the so-called “secretor status,” which is determined by a mutation of the fucosyltransferase gene FUT2 [29, 63]. Additional genetic variants are being evaluated and will likely be added to this list in the future.…”
Section: Recurrent Acute and Chronic Pancreatitis: Distinction And Etmentioning
confidence: 99%
“…Commonly prescribed drugs which are known to be associated with acute pancreatitis are angiotensin-converting enzyme (localized angioedema), statins (direct and accumulation toxicity), oral contraceptives or hormone replacement therapy, especially estrogen (hypertriglyceridemia, local arteriolar thrombosis), diuretics, antiviral therapy (HIV), valproic acid, and antidiabetic agents such as GLP-1 mimetic [25-28]. Interestingly, while it was shown that being the carrier of ABO blood type B increases the risk of developing chronic pancreatitis [29], a recent study has found that the same association exists for drug-induced (i.e., azathioprine-induced) acute pancreatitis in patients with inflammatory bowel disease [30]. …”
Section: Acute Pancreatitis: Definition and Etiologymentioning
confidence: 99%